Olivine anisotropy suggests Gutenberg discontinuity is not the base of the lithosphere - Hansen, L; Qi, C; Warren, J (National Academy of Sciences, 2016)
Tectonic plates are a key feature of Earth’s structure, and their behavior and dynamics are fun-damental drivers in a wide range of large-scale processes. The operation of plate tectonics in gen-eral depends intimately on the manner in which lithospheric plates couple to the convecting inte-rior. Current debate centers on whether the transition from rigid lithosphere to flowing astheno-sph ere relates to increases in temperature or to changes in composition such as the presence of a small amount of melt or an increase in water content below a specified depth. Thus, the manner in which the rigid lithosphere couples to the flowing asthenosphere is currently unclear. Here we present results from laboratory-based torsion experiments on olivine aggregates with and without melt, yielding an improved database describing the crystallographic alignment of olivine grains. We combine this database with a flow model for oceanic upper mantle to predict the structure of the seismic anisotropy beneath ocean basins. Agreement between our model and seismological observations supports the view that the base of the lithosphere is thermally controlled. This model additionally supports the idea that discontinuities in velocity and anisotropy, often assumed to be the base of the lithosphere, are instead intra-lithospheric features reflecting a compositional boundary established at mid-ocean ridges, not a rheological boundary.